Investigation of the criteria for increasing the operational reliability of building frames - Tonkacheev, G.; Rudnieva, I. (Ways to Improve Construction Efficiency, 2021)
Analysis and generalization of previous studies showed that there is no comprehensive solution to the problem of increasing the operational reliability of building frames, reconstruction and modernization of buildings and structures, taking into account a sustainable approach. After the completion of construction, the frame of the building is constantly and steadily changing and wearing out, as a result, requiring an increase in operational reliability, and these processes are associated with the correct decision-making on changing the bearing capacity of structures and on the technology and organization of the corresponding work. To solve this problem, it is necessary to create a general methodology for a system for modeling constructive and technological solutions. The system's methodology is intended to reduce costs while increasing the reliability of frame structures, taking into account social culture, optimal impact on society, efficient use of resources and environmental principles. Particularly acute is the problem of introducing innovative and effective organizational and constructive-technological solutions to ensure the required performance and functionality with a minimum negative impact on the environment, while taking into account the improvement of economic, social, cultural aspects at the local, regional and global levels. In addition, the necessary criteria are an increase of the bearing capacity, a decrease in deformability and the recovery of the operational suitability of building structures. The article investigates a comprehensive solution to the problem of increasing the operational reliability of building frames during the reconstruction and modernization of buildings and structures. Identified internal and external factors of changes, as well as the main criteria for increasing the operational reliability of building frames. Consideration of these factors as a range of functions makes it possible to predict the long-term needs and behavior of the building frame throughout the entire life cycle, taking into account the degradation of building components and the need to restore or strengthen the elements of the building frames. After collecting and analyzing information on the identified factors, a system of technological solutions is proposed that takes into account a sustainable approach to reconstruction and categories such as organizational and technological solutions, structures, materials, economics, management, ecology, social culture, in particular the impact on society and the environment.